Math, asked by bashu1444441, 8 months ago

pls please answer help me pleasee

pls koi galat answer mat dena

jisne notebook mae answer diya aur correct I follow you and thank your answer mark you brilliant​

Attachments:

Answers

Answered by Anonymous
6

See, the formula used here is :-

\sf {(a \pm \dfrac{1}{a})^{2} = a^{2} + \dfrac{1}{a^{2}} \pm 2 }

Now, consider (i)

\sf {x + \dfrac{1}{x} =3 }

This can be written as,

\sf {(x + \dfrac{1}{x} )^{2}=3^{2}}

Then,

\sf {x^{2} + \dfrac{1}{x^{2}} + 2 = 9}

\sf {x^{2} + \dfrac{1}{x^{2}} = 9 - 2}

\sf {x^{2} + \dfrac{1}{x^{2}} = 7}

Now, square this equation :-

\sf {(x^{2} + \dfrac{1}{x^{2}})^{2} = 7^{2}}

Expanding it,

\sf {x^{4} + \dfrac{1}{x^{4}} + 2= 7^{2}}

Now,

\sf {x^{4} + \dfrac{1}{x^{4}} + 2= 49}

\sf {x^{4} + \dfrac{1}{x^{4}} = 49 - 2}

\sf {x^{4} + \dfrac{1}{x^{4}} = 47}

So, your answer is 47

Hope it helps!! :)

Answered by ananya620
0

Answer:

he idk. ..................

Similar questions